Beings of a Feather: Learning About the Lives of Birds with Amazonian Peoples - Jernigan, Kevin (Ethnobiology Letters, 2016)
This article is a memoir of the author’s fieldwork experiences studying traditional knowledge of bird species in the Peruvian Amazon. It describes his growth as a researcher, in light of the practical and methodological challenges of carrying out this kind of work. It also relates how the author’s thinking has evolved on questions of current theoretical interest in ethnobiology. The first section outlines how the author came to be interested in this topic while pursuing an ethnobotanical dissertation project. Next, the discussion follows his work with the indigenous Aguaruna and Iquito peoples, learning about and documenting their understandings of the nesting, foraging and reproductive behavior of local avian species. On one hand, he found that local people provided details of these behaviors that match, in many ways, the counts of academic ornithologists. However, local interpretations of why these behaviors take place are often framed by some very different assumptions. The author uses Victor Toledo’s tripartite framework of kosmos (overarching belief systems), corpus (cognitive categories), and praxis (set of practices) to discuss similarities and differences in Aguaruna, Iquito, and academic ornithology. He also discusses his progression of views on the topic of perspectivism and eventual preference for a theoretical framework favoring a polyontological approach to understanding Amazonian ethnoecology.